Capability, opportunity, and motivation: an across contexts empirical examination of the COM-B model - Taylor Jade Willmott; Bo Pang; Sharyn Rundle-Thiele (BMC, 2021)
Abstract Background There is limited evidence for successful weight gain prevention interventions targeting young adults. Developing effective interventions necessitates a theoretical model that can identify barriers and enablers for healthy eating and physical activity among young adults to support weight management. This study empirically examines the utility of the COM-B model as a framework for intervention planning across two behavioural contexts: eating and physical activity. Methods A cross-sectional survey research design was employed to empirically test the COM-B model in the contexts of young adult's eating and physical activity behaviours. Informed by the Theoretical Domains Framework, pre-validated measures appropriate for capturing the latency of the COM (Capability, Opportunity, and Motivation) constructs were sourced. Both surveys (eating and physical activity) were administered online to two independent samples of young adults aged 18-35 years. Models were specified and tested using structural equation modelling. Results A total of 582 (mean age = 22.8 years; 80.3% female) and 455 (mean age = 24.9 years; 80.8% female) participants were included in the physical activity and eating analyses, respectively. The COM-B model explained 31% of variance in physical activity behaviour and 23% of variance in eating behaviour. In the physical activity model (N = 582), capability and opportunity were found to be associated with behaviour through the mediating effect of motivation. In the eating model (N = 455), capability was found to be associated with behaviour through the mediating effect of motivation. Capability was also found to mediate the association between opportunity and motivation. Consistencies and variations were observed across both models in terms of COM indicators. Conclusions Findings support the COM-B model's explanatory potential in the context of young adult's physical activity and eating behaviours. Barriers and enablers underlying young adult's physical activity and eating behaviours were identified that represent potential targets for future intervention design. Further research is needed to validate present study findings across different populations and settings.